Gestión financiera y su relación con la rentabilidad de la empresa agrícola ler Juez S.A. cantón San Jacinto de Buena Fe, período 2013 - Bravo Guerra, Génesis Abigail (2015)
This thesis entitled "Financial management and its relationship to the profitability of Agrícola SA Ler Judge San Jacinto Canton Good Faith, 2013 period "was performed in order to know the reality of the same and create precedents that help managers make better decisions in profits of the entity. In order to ensure a proper investigation the following objectives; diagnose the current processes and benefits generated by the financial management and define the level of profitability of the company for purposes of the management model used. To support the work concepts, definitions, theories and laws of authors refer to the topic under study were used. This work was done using the historical, analytical, inductive, deductive and observational method, whereas the types of research were; field, descriptive literature, on how these techniques interview and survey were based. The research results showed that in Agricultural Ler Judge financial management processes are used as; planning, organizing, directing, monitoring and evaluation of activities. The advantages that the financial management system has resulted in the state are; proper handling and reliability of accounting information, timely financial processes, suitable internal control, compliance with the objectives and equitable distribution of economic resources, material, technological and human. Regarding the level of profitability that is favorable to business growth, reflecting a timely return.